(NpROIZWEDENIQ (B1906-1914 (NGODOW (B/s (N~ASTX (B1s - (NpRI[WIN(B, (NmIHAILs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1982)
(Nw PERWYJ TOM WOSXMITOMNOGO SOBRANIQ SO^INENIJ m(B.(Nm(B. (NpRI[WINA (B(!873-1954) (NPOME]ENY EGO RANNIE PROIZWEDENIQ(B, (NW TOM ^ISLE TAKIE IZWESTNYE(B, (NKAK (B"(Nw KRA@ NEPUGANYH PTIC(B", "(NzA WOL[EBNYM KOLOBKOM(B" (NI DR(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs